Moderation of Contingency Factors on the Effect of Fiscal Decentralization Inequality between Regencies/Cities in the Province of Bali - Dwirandra, Anak Agung Ngurah Bagus (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 1 (2021), 2021)
Fiscal decentralization affects inequality between regions but is not always linear because of contingent factors. The purpose of this study is to confirm the effect of fiscal decentralization on inequality between regions in the Bali Province. Specifically, this research aims to examine the moderating effect of contingent factors, such as regional spending, private investment, and general allocation funds, on fiscal decentralization. Secondary data published on the local government/municipal government website and Bali provincial statistics agency were used. Data were analyzed using moderated regression analysis techniques. Results conclude that fiscal decentralization has no significant negative effect on inequality between regions. Both regional expenditures and general allocation funds are unable to moderate the negative effect of fiscal decentralization on inequality between regions. On the other hand, private investment moderates the negative effect of fiscal decentralization on inequality between regions. Keywords : fiscal decentralization, inequality between regions/cities, regional spending, private investment, general allocation funds.